Adoption and impact of fertiliser trees on heterogeneous farmer classified soil types in the Chongwe district of Zambia. Issue 2 (3rd April 2018) - Kuntashula, Elias; Nhlane, Robert; Chisola, Fulayi
ABSTRACT: Adoption of fertiliser trees in Zambia remains very low while efforts to understand the farmers' decision-making process in embracing sustainable agricultural practices still eludes research. One area not vigorously pursued in understanding the farmers' adoption process is the role that farmer classification of on-farm soils plays in adoption and impact of sustainable technologies such as the fertiliser trees. Therefore, the objective of this study was to estimate adoption rates and impact of fertiliser trees on heterogeneous soil types according to farmers' classifications. Using data randomly collected from 324 households in the 2011 farming season in Chongwe district of Zambia, it was found that farmers were able to classify the dominant soils on their farms into sandy, clay, sand loamy and loamy soils. Most of the farmers (60%) who perceived their soils to be sandy also indicated facing soil fertility challenges. Perception of being on sandy soils was significantly associated with adoption of the fertiliser trees. Propensity score estimates showed that the technology significantly increased maize productivity on soils perceived to be sandy and sand loamy. The non-significant impact results of the technology on relatively perceived high fertile loamy and clay soils could be indicative of diminishing marginal effect of the technology on already fertile soils. Although adoption of the technology on relatively fertile soils is important for fertility sustainability, its promotion on farms with degraded soils could ensure full expression of its potential, and hence, increase its adoptability chances. Targeting of farmers who receive fertiliser tree seedlings should embrace this condition.